2016
DOI: 10.1080/15384047.2016.1139247
|View full text |Cite
|
Sign up to set email alerts
|

Validating the disruption of proliferating cell nuclear antigen interactions in the development of targeted cancer therapeutics

Abstract: Human DNA replication and repair is a highly coordinated process involving the specifically timed actions of numerous proteins and enzymes. Many of these proteins require interaction with proliferating cell nuclear antigen (PCNA) for activation within the process. The interdomain connector loop (IDCL) of PCNA provides a docking site for many of those proteins, suggesting that this region is critically important in the regulation of cellular function. Previous work in this laboratory has demonstrated that a pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In this study, we show that R9-caPeptide inhibits replication fork progression, causes DNA damage, and ultimately leads to apoptosis of pancreatic cancer cells. [21][22][23] Importantly, R9-caPeptide is minimally toxic to normal or non-cancerous immortalized cells as reported in our previous work. 19,21 The observed inhibition of replication progression is likely mediated through disruption of PCNA-FEN1 and PCNA-LIG1 interactions that are important in the maturation of Okazaki fragments, compromising replication fork progression, as shown previously.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, we show that R9-caPeptide inhibits replication fork progression, causes DNA damage, and ultimately leads to apoptosis of pancreatic cancer cells. [21][22][23] Importantly, R9-caPeptide is minimally toxic to normal or non-cancerous immortalized cells as reported in our previous work. 19,21 The observed inhibition of replication progression is likely mediated through disruption of PCNA-FEN1 and PCNA-LIG1 interactions that are important in the maturation of Okazaki fragments, compromising replication fork progression, as shown previously.…”
Section: Discussionsupporting
confidence: 74%
“…We showed that caPeptide inhibited in vitro DNA replication due to its ability to disrupt specific PCNA interactions with various DNA replication components, including Pol d and FEN1. 21,22 Furthermore, when attached to an R9 peptide (nine arginines) for cellular delivery, the R9-caPeptide exhibited cytotoxicity in breast and neuroblastoma cancer cell lines. It was also shown that R9-caPeptide is non-toxic to non-malignant cell lines, such as human peripheral blood mononuclear cells, human neural crest stem cells, and human mammary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…A cell permeable peptide (R9-caPep) containing the L126-Y133 sequence of PCNA selectively blocks PCNA interactions in cancer cells and interferes with DNA synthesis and HR-mediated DSB repair, resulting in S-phase arrest, an accumulation of DNA damage, and an enhanced sensitivity to cisplatin [9]. R9-caPep also selectively kills cancer cells with much less toxicity to human peripheral blood mononuclear cells or neural crest stem cells and suppresses cell growth in a mouse xenograft model without causing any discernable toxicity to the animals [9,[185][186][187]. These findings demonstrate that targeting protein-protein interactions involving the L126-Y133 region of PCNA may prove to be an effective approach to treating cancers with reduced side effects.…”
Section: Targeting Pcna the "Hub" Protein Of Dna Replication And Repa...mentioning
confidence: 99%
“…R9-caPeptide was found to disrupt interaction of PCNA with its binding partners. Surface plasmon resonance studies showed disruption of PCNA with a peptide from FEN1 and the p66 subunit of DNA polymerase δ (POLD3) [ 105 , 106 ]. Additionally, caPeptide was found to interact with POLD3 [ 107 ].…”
Section: Rational Of Targeting Pcna-binding Proteins With a Peptide Derived From Cancer-associated Pcnamentioning
confidence: 99%